Intraoperative Angiography Provides Objective Assessment of Skin Perfusion in Complex Knee Reconstruction. Issue 1 (January 2015) - Wyles, Cody C.; Taunton, Michael J.; Jacobson, Steven R.; Tran, Nho V.; Sierra, Rafael J.; Trousdale, Robert T.
Abstract: Background: Wound necrosis is a potentially devastating complication of complex knee reconstruction. Laser‐assisted indocyanine green angiography (LA‐ICGA) is a technology that has been described in the plastic surgery literature to provide an objective assessment of skin perfusion in the operating room. This novel technology uses a plasma protein bound dye (ICG) and a camera unit that is calibrated to view the frequency emitted by the dye. The intention of this technology is to offer real‐time visualization of blood flow to skin and soft tissue in a way that might help surgeons make decisions about closure or coverage of a surgical site based on blood flow, potentially avoiding soft tissue reconstruction while preventing skin necrosis or wound breakdown after primary closures, but its efficacy is untested in the setting of complex TKA. Questions/purposes: The purpose of this study was to evaluate perfusion borders and tension ischemia in a series of complex knee reconstructions to guide optimal wound management. Methods: Beginning in mid‐2011, an LA‐ICGA system was used to evaluate soft tissue viability in knee reconstruction procedures that were considered high risk for wound complications. Seven patients undergoing complex primary or revision TKA from 2011 to 2013 were included. These patients were chosen as a convenience sample of knee reconstruction procedures for which we obtained consultation with the plastic surgery service. The perfusion of skin and soft tissue coverage was evaluated intraoperatively for all patients with the LA‐ICGA system, and the information was used to guide wound management. Followup was at a mean of 9 months (range, 6‐17 months), no patients were lost to followup, and the main study endpoint was uneventful healing of the surgical incision. Results: All seven closures went on to heal without necrosis. One patient, however, was subsequently revised for a deep periprosthetic infection 4 months after their knee reconstruction and underwent flap coverage at the time of that revision. Conclusions: Implementation of LA‐ICGA provides an objective intraoperative assessment of soft tissue perfusion. This technology may help guide the surgeon's decisions about wound closure in real‐time to accommodate the perfusion challenges unique to each patient. Specifically, patients with medical risk factors for poor perfusion or wound healing (such as diabetes, peripheral vascular disease, tobacco use, corticosteroid therapy, infection) or anatomical/surgical risk factors (ie, previous surgery about the reconstruction site, trauma wounds, or reconstruction of severe deformity) may benefit from objective intraoperative information regarding perfusion of the wound site. Furthermore, LA‐ICGA could be used to prospectively evaluate the physiologic impact of different wound closure techniques. Level of Evidence: Level IV, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.